Assessment of diagnostic criteria between primary cutaneous anaplastic large‐cell lymphoma and CD30‐rich transformed mycosis fungoides; a study of 66 cases. (16th May 2015) - Fauconneau, A.; Pham‐Ledard, A.; Cappellen, D.; Frison, E.; Prochazkova‐Carlotti, M.; Parrens, M.; Dalle, S.; Joly, P.; Viraben, R.; Franck, F.; Ingen‐Housz‐Oro, S.; Giacchero, D.; et al.
Summary Background Transformed mycosis fungoides (TMF) large cells may express CD30 antigen, and because of this, the differential diagnosis between CD30‐rich TMF and primary cutaneous anaplastic large‐cell lymphoma (cALCL) may be difficult, and especially in distinguishing cALCL associated with MF vs. CD30‐rich TMF. Objectives To find clinical, histological and molecular diagnostic features useful for differential diagnosis between cALCL and CD30‐rich TMF. To analyse and compare the prognostic value of clinical and pathological factors in these two diseases. Material and methods We conducted a retrospective study (1999–2012) of 32 patients with cALCL and 34 with CD30‐rich TMF, seen in reference centres of the French Study Group of Cutaneous Lymphoma. Clinical, histological and molecular features were analysed and compared to determine their diagnostic and prognostic value. Results Comparison of the two groups showed that age ˃ 60 years, ≥ 5 skin lesions, early progression, absence of spontaneous regression and trunk involvement were significantly associated with the diagnosis of TMF. Abnormal T‐cell phenotype and perforin expression were significantly more frequent in cALCL (both P < 0·001). Overall survival (OS) at 5 years was 77·4% for cALCL and 20·7% for CD30‐rich TMF. Stage T3, ≥ 5 skin lesions, lower limb involvement for cALCL and stage T4, extracutaneous involvement, B symptoms, high levels of lactate dehydrogenase for CD30‐rich TMF were associated with poor OS and progression‐free survival. DUSP22 gene rearrangement had no diagnostic or prognostic value. Conclusions Clinical features and outcome are the most discriminative to differentiate the two entities. Even histological and molecular markers were not fully specific; abnormal vs. normal T‐cell phenotype and perforin expression may constitute helpful tools.